Know Your Customer Principle as a Measure to Prevent Money Laundering In Banking (Study at BSI KCP Banjarmasin A. Yani) - Rahmiyati, Maulida; Rimayanti (Sharia Journal and Education Center Publishing, 2024)
Abstract This research is motivated by the problem of implementing the Know Your Customer Principle which can be seen through the implementation of customer acceptance policies, and procedures for identifying customers and monitoring procedures for customer accounts and transactions. This research aims to find out the implementation of Know Your Customer Principles in Sharia banking and also to find out how to prevent Money Laundering carried out by BSI KCP Banjarmasin A.Yani. This research is field research with a qualitative descriptive approach. The location of this research was carried out at Bank Syariah Indonesia (BSI) KCP Banjarmasin A. Yani. The results of this research reveal that the implementation of the Know Your Customer Principle has been carried out optimally with customer identification procedures and the use of the BISA Application in the context of implementing the Know Your Customer Principle. Apart from that, by having internal supervision of customers and the customer acceptance process is also carried out strictly, through identification and verification of customer data to avoid the entry of customers with bad intentions to the bank, this can prevent the crime of Money Laundering. Keywords: Know Your Customer Principle; Money Laundering; Bank Syariah Indonesia Abstrak Penelitian ini dilatarbelakangi oleh permasalahan penerapan Prinsip Mengenal Nasabah yang dapat dilihat melalui penerapan kebijakan penerimaan nasabah, dan prosedur identifikasi nasabah serta prosedur pemantauan terhadap rekening dan transaksi nasabah. Penelitian ini bertujuan untuk mengetahui penerapan Prinsip Mengenal Nasabah pada perbankan Syariah dan juga untuk mengetahui cara pencegahan Pencucian Uang yang dilakukan oleh BSI KCP Banjarmasin A.Yani. Penelitian ini merupakan penelitian lapangan (field research) dengan pendekatan deskriptif kualitatif. Lokasi penelitian ini dilakukan di Bank Syariah Indonesia (BSI) KCP Banjarmasin A. Yani. Hasil penelitian ini mengungkapkan bahwa penerapan Prinsip Mengenal Nasabah telah dilakukan secara optimal dengan adanya prosedur identifikasi nasabah dan penggunaan Aplikasi BISA dalam rangka penerapan Prinsip Mengenal Nasabah. Selain itu, dengan adanya pengawasan internal terhadap nasabah dan proses penerimaan nasabah juga dilakukan secara ketat, melalui identifikasi dan verifikasi data nasabah untuk menghindari masuknya nasabah yang beritikad tidak baik ke bank, maka hal ini dapat mencegah terjadinya tindak pidana Pencucian Uang. Kata kunci: Prinsip Mengenal Nasabah; Pencucian Uang; Bank Syariah Indonesia